2016
DOI: 10.29252/ijrm.14.12.743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of insulin sensitizers metformin and pioglitazone alone and in combination on women with polycystic ovary syndrome: An RCT

Abstract: Background:Insulin resistance and hyperinsulinemia may play a role in pathogenesis of PCOS. One of the common therapeutic methods is using insulin-sensitizing drugs such as metformin and thiazolidinediones.Objective:The purpose was to determine the effect of metformin and pioglitazone on clinical, hormonal and metabolic parameters in women with PCOS.Materials and Methods:Eighty four women randomly received one of the following for 3 months: metformin (n=28) (500 mg three times a day), pioglitazone (30 mg daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 70 publications
2
64
1
Order By: Relevance
“…Total 486 related articles were extracted from the three databases and 436 articles were left after removing duplication. Finally, 11 articles meeting the criteria [ 16 26 ] were left after the abstract and the full text had been read. Figure 1 shows the search strategy for selection of trials.…”
Section: Resultsmentioning
confidence: 99%
“…Total 486 related articles were extracted from the three databases and 436 articles were left after removing duplication. Finally, 11 articles meeting the criteria [ 16 26 ] were left after the abstract and the full text had been read. Figure 1 shows the search strategy for selection of trials.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin is one of the most efficient drugs for the treatment of type 2 diabetes and also acts as insulin sensitizer [37,50]. Our results demonstrated that metformin has no difference in average body weight with HFD-treated group, but it was observed treatment with metformin decrease the average body weight when compared with before metformin treatment.…”
Section: Discussionmentioning
confidence: 49%
“…They concluded that insulinsensitizing drugs induce beneficial effects in insulin resistance and menstrual cycle, but only metformin aided in reducing hyperandrogenemia in women with PCOS. 23 These findings further evidence the fact that metformin has real potential in eliminating clinical signs and symptoms of PCOS.…”
Section: Findings Metformin Use In Pcosmentioning
confidence: 63%
“…16,17 Weight reduction and lifestyle modification should be considered first-line treatment for BMI and cardiovascular risk reduction Propst et al, 2,3 but metformin can be a suitable alternative for obese or overweight women with insulin resistance. 5,11 Metformin is the only insulinsensitizing drug that has succeeded in decreasing hyperandrogenemia in women with PCOS Mojtaba Sohrevardi et al, 23 and has also been shown to decrease body weight Du et al 31 as well as to regulate the menstrual cycle. 18 Metformin and clomiphene-citrate combined have also been shown to be more effective than the placebo in inducing ovulation in women with clomid-resistant PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation